Power-to-hydrogen concepts for 100% renewable and sustainable energy systems - Nikolaidis, Pavlos; Poullikkas, Andreas (My University, 2023)
The increase of energy demand and reduction in resources for conventional energy generation have promoted the use of renewable energy sources for energy production. As the only carbon-free with the highest energy content compared to any known fuel, H2 is globally accepted as an environmentally benign renewable energy carrier, alternative to fossil fuels. Based on the feedstocks used, the various processes for its production are generally distinguished in reforming, nonreforming, and water-splitting. In the context of sustainable development, electrolytic power-to-hydrogen mechanism constitutes a potential candidate capable of satisfying all aspects of the energy trilemma, namely affordability, reliability, and sustainability, and providing the pathway for 100% renewable and sustainable energy systems. Considering large and cost-efficient centralized hydrogen production plants, some management-based challenges regard the utilization factor, product purity, storage, transport and distribution, and safety issues. However, the flexibility from power-to-hydrogen plant makes it profitable through reasonable operation among multiple energy sectors, while ensuring universal access to energy, reducing the associated with energy greenhouse gas emissions, enhancing the energy security, minimizing overall costs, creating opportunities for more local jobs, and eliminating the risk over nuclear accidents and nuclear proliferation.
Keywords: 100% renewable systems; Hydrogen economy; Power-to-hydrogen process; Renewable energy sources; Water electrolysis